2021
DOI: 10.1371/journal.pntd.0009500
|View full text |Cite
|
Sign up to set email alerts
|

Lay attitudes and misconceptions and their implications for the control of brucellosis in an agro-pastoral community in Kilombero district, Tanzania

Abstract: Brucellosis is a priority zoonotic disease in Tanzania that causes ill-health in people and affects livestock productivity. Inadequate awareness and behavior risking transmission can impede control efforts. We conducted a cross-sectional survey of 333 livestock owners in three villages in the Kilombero district, Tanzania, to understand their awareness, knowledge and behavior associated with brucellosis. Six Focus Group Discussions (FGDs), two in each village, were conducted, as well as an additional FGD with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…As such, being male and young (aged 40 years or less) was negatively associated with promptly seeking treatment for fever. These findings are consistent with what Mbruru et al (56) found in a study of lay attitudes of animal to human infections, and how etiologies of febrile illness potentially caused by animalhuman interaction influence men and women's treatmentseeking behavior. In our study, and as we describe in detail later, power relations at community and household level shape access to medical resources, including medical fees, money for buying OTC medication, interpretation of illness symptoms or time allocation for gathering herbal treatment from the forest.…”
Section: Lay Etiologies Of Febrile Illnesssupporting
confidence: 90%
“…As such, being male and young (aged 40 years or less) was negatively associated with promptly seeking treatment for fever. These findings are consistent with what Mbruru et al (56) found in a study of lay attitudes of animal to human infections, and how etiologies of febrile illness potentially caused by animalhuman interaction influence men and women's treatmentseeking behavior. In our study, and as we describe in detail later, power relations at community and household level shape access to medical resources, including medical fees, money for buying OTC medication, interpretation of illness symptoms or time allocation for gathering herbal treatment from the forest.…”
Section: Lay Etiologies Of Febrile Illnesssupporting
confidence: 90%
“…Such behaviors are practiced regardless of the knowledge of spread of zoonotic pathogens. This is supported by the study conducted in an agropastoral community where agro-pastoralists engaged in risky behaviors, although they knew the existence of a zoonotic disease [ 18 ]. They attributed the risky behaviors to culture, social norms, and the belief that the risk is low since they have been practicing those behaviors for generations without any health implication.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this finding emphasizes the well-known association between spontaneous abortion in animals and brucellosis infection [ 48 , 49 ]. Despite the established link between brucellosis and spontaneous abortion in livestock, pastoralists may not always associate spontaneous abortions in their animals with brucellosis [ 50 ]. As a result, they may continuously expose themselves to the disease while handling infected abortion materials.…”
Section: Discussionmentioning
confidence: 99%